Silvopastoral systems in the subtropical and temperate zones of South America: an overview. - Peri, Pablo Luis; Dube, Francis; Costa Varella, Alexandre (Springer, 2021)
In the subtropical and temperate zones of South America (Argentina, Chile and Southern Brazil), silvopastoral systems have become an economical, ecological and productive alternative. These systems incorporate exotic tree species or managed native forests into farming systems allowing the production of trees and livestock from the same unit of land. This provides diversification of farm income, either directly from the sale of timber and animals, and/or indirectly by the provision of stock shelter and beneficial effects on soil conservation. Thus, these systems can be more biologically productive, profi table and sustainable than forestry or animal production monocultures. However, livestock grazing is one of the most widespread land uses in South America and is arguably the land use that has had the greatest impact on regional biodiversity. This multi-authored book is a compendium of original research articles, case studies, and regional overviews that summarizes the current state of knowledge on different components and aspects (pasture, animal and trees productions, carbon sequestration, and conservation) of silvopastoral systems in native forests and tree plantations.